2020
DOI: 10.1016/j.chom.2020.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Env Exceptionalism: Why Are HIV-1 Env Glycoproteins Atypical Immunogens?

Abstract: Recombinant HIV-1 envelope (Env) glycoproteins of ever-increasing sophistication have been evaluated as vaccine candidates for over 30 years. Structurally defined mimics of native trimeric Env glycoproteins (e.g., SOSIP trimers) present multiple epitopes for broadly neutralizing antibodies (bNAbs) and their germline precursors, but elicitation of bNAbs remains elusive. Here, we argue that the interactions between Env and the immune system render it exceptional among viral vaccine antigens and hinder its immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
52
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 159 publications
4
52
0
Order By: Relevance
“…All are key features to be considered in vaccine design. Our findings add substantially to earlier reports of sporadic or low-titer neutralization of heterologous tier 2 viruses elicited in RMs by SHIVs bearing lab-adapted or animal passaged HIV-1Envs(61)(62)(63)(64) or Env immunogens(65)(66)(67)(68)(69)(70)(71)(72). Unlike previous reports, the current results show how closely neutralizing antibody responses in RMs can mirror responses in humans and indicate the extent to which protective responses elicited by reverse engineered or lineage-based vaccines in RMs might be expected to predict human responses to candidate vaccines(10,11,73,74).A surprising observation was the extent to which Env evolution in multiple rhesus animals recapitulated evolution of homologous Envs in human infections.…”
supporting
confidence: 86%
“…All are key features to be considered in vaccine design. Our findings add substantially to earlier reports of sporadic or low-titer neutralization of heterologous tier 2 viruses elicited in RMs by SHIVs bearing lab-adapted or animal passaged HIV-1Envs(61)(62)(63)(64) or Env immunogens(65)(66)(67)(68)(69)(70)(71)(72). Unlike previous reports, the current results show how closely neutralizing antibody responses in RMs can mirror responses in humans and indicate the extent to which protective responses elicited by reverse engineered or lineage-based vaccines in RMs might be expected to predict human responses to candidate vaccines(10,11,73,74).A surprising observation was the extent to which Env evolution in multiple rhesus animals recapitulated evolution of homologous Envs in human infections.…”
supporting
confidence: 86%
“…The protein surface of Env is almost completely shielded by glycans, which contributes to its poor immunogenicity 13 . Env and Env-based vaccines, including nativelike SOSIP trimers and SOSIP-based clinical candidates, have holes in their glycan shield from two different sources.…”
Section: Introductionmentioning
confidence: 99%
“…It has been repeatedly reported that the charge of liposome-based vaccines determines their fate (i.e., retention at the point of injection, cellular uptake, and lymph-node trafficking) and the type of immune response they may elicit [ 80 ]. The objectives of particulate display of Env trimers are, inter alia, increased lymph-node trafficking and enhanced B cell engagement [ 2 , 4 , 5 , 6 , 7 , 8 , 9 ]. Although several studies have shown that positively charged liposomes can indeed be delivered to lymph nodes, further research is required to assess whether their use within the context of nanoparticle-based HIV-1 vaccines is indicated/useful at all [ 81 , 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the introduction of these well-conceived immunogen constructs and the use of new and elaborate immunisation strategies, inducing the desired type of immune response remains a major challenge. The reasons for this are multifaceted and have recently been discussed elsewhere [ 2 , 3 ]. The nanoparticulate display of native-like Env trimers and other state-of-the-art HIV immunogens has long been regarded as a promising strategy to improve and shape immune responses [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation